APPLICATION OF GEOSPATIAL TECHNIQUES IN THE LOCATIONAL PLANNING OF HEALTH CARE CENTERS IN MINNA, NIGERIA - Oluwaseun Olubadewo-Joshua; Kenneth Michael Ugom (Department of Geography Education, University of Jember, 2018)
Access to health care is an important component of an overall health system and a major indicator of growth. Health care planning and Geographic Information System (GIS) are two relevant fields that depend upon spatial data. GIS plays an essential role in helping public health organizations to understand population health and make decisions with the powerful tools and situation that GIS technology provides. The purpose of the study to investigated the spatial distribution of health care centers in Minna, Nigeria with a view to use Geographic Information System (GIS) technique in health care management and planning. The method is a qualitative research that is used in making decisions in order to have a strong understanding of government policies and programs. Beyond the many uses of a GIS in health applications, the greatest power of a GIS lies in its ability to integrate information from disparate sources. Traffic disturbances and poor road network were observed to be the major factors militating against effective health care facilities location in the study area. Keywords: Geographic Information Systems, Healthcare, Planning, Remote Sensing, Research References ReferencesAbbas, I.I, Auta, S.Z and Naâ€™iya, R.M (2012) Health Care Facilities Mapping and Database Creation Using GIS in Chikun Local Government, Kaduna State, Nigeria. Global Journal of Human Social Sciences (B) Vol. XII, Issue X, Version 1, pp 10-18 Abegunde, A.A.and Adedigba, A.M. (2011). Teaching Hospitals in African Nations: Infrastructure for Regional or Local Community Development? The African Symposium, Vol. 11, No. 2, p 49-59 Abubakar, M.S, Dalhatu, U. and Adamu M.Y (2008) Creating a GIS application for local health care planning in Nassarawa State. Indian Journal of Multidisciplinary Research; 4(4)557-592 Adejuyigbe, O. (1973), Location of Social ServiceCentresin Western Nigeria, The case of Medical Facilities, Man and Society.1, 115-142 Agaja, S.A (2012) Spatial Distribution of Primary Health Care Centers in Ughelli South and Warri South Local Government Areas of Delta State, Nigeria. International Journal of Scientific and Technology Research. 1(9):38-41 Ajala, O.A., Sanni, L. and Adeyinka, S.A. (2005), Accessibility to Healthcare Facilities: A Panacea for Sustainable Rural Development in Osun State, South Western Nigeria. Journal of Human Ecology,18(2), 121-128 Albert, D.P, Gesler, W.M and Levergood, B. (2000), Spatial Analysis, GIS, Remote Sensing applications in the Health Sciences. Ann Arbor Press, Chelsea, Michigan. Andersen, R.M., (1995) â€œRevisiting the behavioral model and access to medical care,Journal of Health and Social Behavior,36(1), 1-10 Arnoff, S. (1989), Geographic Information Systems: A Management Perspective. Ottawa, Ontario: WDL Publications Ayeni B. (1987) Improving the Geographical Accessibility of Health Care Delivery Facilities in Rural Areas; A Nigerian case Study. Social Sciences and Medicine.Vol. 25 No. 10 pp. 1083-1094 Barton, H. and Isourou, C. (2000),Healthy Urban Planning. Spoon Press: WHO Regional Office for Europe Burrough, P.A (2001), GIS and Geostatistics: Essential partners for spatial analysis. Environmental and Ecological Statistics, 8:361-377 Cromley, E.K and McLafferty, S.L (2012),GIS and Public Health. The Guilford Press, New York, London. 2ndEdChang, K. (2008), Introduction to Geographic Information Systems. Boston: McGraw Hill Densham, P.J. (1994) Integrating GIS and Spatial Modeling: Visual Interactive Modeling and Location Selection, Geographical Systems, 1(3), 203-219 Dermatis, Z., Tsoromokos, D., Gozadinos, F., and Lazakidou A. (2016) The utilization of Geographic Information System in Healthcare. International Journal of Health Research and Innovation.Vol. 4 No.1 pp39-57 Egunjobi, L.(1983) Factors Influencing the Choice of Hospitals: A Case study of the Northern part of Oyo State, Nigeria. Social Science and Medicine, Vol. 17, No.9, pp. 585-589 Fabiyi, S. (2001) Geographic Information Systems: Techniques and Methods RSS1, Ibadan Frank, T. (2006) Methodology for optimizing location of new primary health care facilities in rural communities: A case study in KwaZuluâ€Natal, South Africa Gatrell, A.C and Elliott, S.J (2009), Geographies of Health: An Introduction. Malden, MA: Wiley-Blackwell, 2ndEd. Goldman, N. and Pebley, A.R. (1994) Health Cards, Maternal Reports and the Measurement of Immunization Leverage: the Example of Guatemala. Social Science and Medicine Jimoh, H.I. and Azubike, J.O. (2012), The Roles of Geographic Information System on the Distributional Pattern of Health Care Facilities in Ilorin, Kwara State of Nigeria, International Journal ofSocialScience& Education, Vol. 2 (2), 224-235 Joseph, A.E. and Philips, D.R. (1984) Accessibility and Utilization: Geographical perspective on Health Care Delivery; London, Harperand RowKalogirou, S. and R. Foley (2006), Health, Place and Hanly: Modeling Accessibility to Hospitals in Ireland. Irish Geography, 39 (1), pp. 52-68 Knox, P.L. (1979), The Accessibility of Primary Care to Urban Patients: A Geographical Analysis. British Journal of General Practice, 29, pp. 160-168 Kufoniyi, O. (1998) Education requirements in Geospatial Information Technology, Proceedings of the Workshop on Surveying and Spatial Information Technology, University of Lagos, Nigeria, 13p Law, M.R and Morris, J.R (1998) Why is mortality higher in poorer and in more Northern areas of England and Wales? Journal of Epidemiology Community Health, 52:344-352 Lekan, S. (2010), Distributional Pattern of Healthcare Facilities in Osun State, Nigeria. Ethiopian Journal of Environmental Studies and Management, Vol. 3, No2 McLafferty, S.L (2003) GIS and Healthcare. Annual Reviews on Public Health. 2003.24:25-42. www.annualreviews.org MitropoulosP, MitropoulosI, Giannikos I. and Sissouras, A. (2006), A Biobjective Model for the Locational Planning of Hospitals and Health Centers. Health Care Management Science, 9:171-179 Nkechi,C. (2013), Spatial analysis of health care facilities in Lapai LGA, Unpublished Bsc Project, IBB University, Lapai. Ogundare, E.I (1982), Health Care Delivery is a Success in Oyo state, Daily Sketch, October 27, p.7 Okafor, F.C., (1990), The Spatial Dimensions of Accessibility to General Hospitals and Rural Nigeria. Socio-Economic Planning Sciences, 24 (4), pp. 295-306 Olajuyin, L.O, Olayiwola, L.M and Adeyinka, S.A. (1997) Locational analysis of Health Facilities: A case study of Irewole LGA (1940-1985). Ife Planning Journal: A Journal of Ife Community Development Study Team (ICOMDEST). 1(1), 1-13 Oppong,J.R., (2007) Data Problems in GIS and Health. Retrieved from: geog.queensu.ca/h_and_e/ healthandenvir/.../OPPONG.DOC Parker E.B andCampbell J.L. (1998) Measuring access to primary medical care: some examples of the use of geographical information systems. Health & Place. 4(1)83-93 Perry, B., and Gesler, W. (2000). Physical Access to Primary Health Care in Andean Boliva. Social Science Medicine, 50(11)77-88 Rushton, G., and Lolonis, P.(1996) Exploratory Spatial Analysis of Birth Defect Rates in an Urban Population. Statistics in Medicine 15:717-726 Tomlin C.D. (1990) Geographic Information Systems and Cartographic Modeling, Prentice Hall Ufua, M.E. (2002): The Use of SPOT Remotely Sensed Data for the Revision of Nigerian 1:50,000 Topographic Maps. In Uluocha, O.N.Dada, F.A.O. (eds), Maps and Resource Management Publication of Nigerian Cartographic Association P98-113 Uluocha, O.N. (2007) Elements of Geographic Information Systems. San Iroanusi Publication, LagosUsman, A.K and Ahmed, M. (2013) Distribution of Primary Healthcare facilities in Kano Metropolis using Geographic Information Systems. Research Journal of Environmental and Earth Sciences.5(4):167-176 Vatsavai, R.R., Burk, T.E., Wilson, B.T., and Shekhar, S. (2000). A Web-based browsing and spatial analysis system for regional natural resource analysis and mapping. In Proceedings of 8th ACM Symposium on GIS, Washington, D.C., USA, pgs 95-101 Wang F.H,andLuo W. (2005) Assessing spatial and non spatial factors for healthcare access: towards an integrated approach to defining health professional shortage areas, Health & Place. 11:131-46 Wenger, E., McDermot, R., and Synder, W. M. (2002), Cultivating communities of practice: A guide for managing knowledge.Boston: Harvard Business School Press Wilkinson, R and Marmot, M (2006), Social Determinants of Health, International Journal of Epidemiology,35(4)1111-1112.World Health Organization (1998), The World Health Report 1998-Life in the 21stCentury: A vision for all World Health Organization (2000), The World Health Report 2000-Health Systems: Improving PerformanceWorld Health Organization (2004), The World Health Report 2004-GIS and Public Health MappingWorld Health Organization (2008), The World Health Report 2008-Primary Health Care now more than ever Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License